2012
DOI: 10.1016/j.eatbeh.2011.11.012
|View full text |Cite
|
Sign up to set email alerts
|

Do exercise motives predict obligatory exercise?

Abstract: Few studies have examined whether factors predicting obligatory exercise differ by gender. 303 participants completed the Obligatory Exercise Questionnaire and the Reason for Exercise Inventory. All variables correlated significantly. However, the correlation between exercising for fitness and obligatory exercise was significantly stronger in women than men. In women, obligatory exercise was predicted by exercising to improve body tone, fitness, and to enhance mood; in men, obligatory exercise was predicted by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 19 publications
(26 reference statements)
1
8
0
1
Order By: Relevance
“…A specific predictor of CE in HC was stress management. This is in line with Pritchard and Beaver [ 46 ] who found that obligatory exercise was predicted by exercise for mood improvement in healthy women.…”
Section: Discussionsupporting
confidence: 91%
“…A specific predictor of CE in HC was stress management. This is in line with Pritchard and Beaver [ 46 ] who found that obligatory exercise was predicted by exercise for mood improvement in healthy women.…”
Section: Discussionsupporting
confidence: 91%
“…This approach is consistent with the recognition that it is important for researchers to distinguish between different aspects of narcissism in order to develop a more complete and nuanced understanding of the attitudes and behaviors that characterize narcissism. Exercise-related motives have been found to be associated with a range of attitudes and behaviors concerning exercise [47,59] as well as exercise addiction [60]. However, there are various approaches available for conceptualizing exercise-related motives [61,62].…”
Section: Overview and Predictionsmentioning
confidence: 99%
“…One barrier to consensus has been the considerable number of terms used to define the construct of ME, which vary in both the degree to which they quantify exercise (i.e., excessive nature) or in their qualitative nature (i.e., motivation for engaging in exercise behavior). Some of these constructs include “compulsive” (Meyer et al, 2011); “exercise dependence” (Hausenblas & Downs, 2002b); “obligatory” (Pritchard & Beaver, 2012), “addictive” (Adams & Kirkby, 2002), and “driven” (Stiles‐Shields et al, 2015), among others. ME has also been defined as either a primary disorder (functioning to reduce negative affect) or a secondary symptom of an ED (functioning to control weight and shape) (Bamber et al, 2003), and research distinguishing these forms of problematic exercise typically qualifies primary pathological exercise as addictive and secondary pathological exercise as compulsive (Cunningham et al, 2016).…”
Section: Introductionmentioning
confidence: 99%